Sistem Informasi Sumber Daya Manusia (SISDM) Dalam Proses Penentuan Karyawan Tetap Dengan Menggunakan Metode AHP (Analytical Hierarchy Process ) - Ali Ibrahim; Ria Anggraini (Annual Research Seminar (ARS), 2016)
Abstract—Human Resources Information System (HRIS) is an information system that used to store, manage, and provide an output for a company or organization. The presence of a human resources information systems within the company or organization will facilitate the work involved in the company. As well as in PT. Konverta Mitra Abadi Palembang, on the process of deciding the permanent employee are not really optimal or not yet had the decision support system to decide the permanent employee . and then the solution for these problems are designed a system with the information system development method used the method of HRIS and decision-making method using the Analytical Hierarchy Process (AHP). AHP is a method that effective to solving complex problems and accelerate the decision-making process. In the process of deciding the permanent employee at PT Konverta Mitra Abadi Palembang there are some criteria on which to base decisions, among others, operational performance, general assessment and attendance. Operational performance has subcriteria the achievement of the target, work consistent, and productivity. General assessment has subcriteria work attitude, team work, initiative, leadership and leadership potential while attendance has subcriteria personal affair, come late, go home early, forget to note and absent. This system was developed using HTML and PHP programming language and uses a MySQL database to produce a human resource information system in the process deciding the permanent employee.Keywords: HRIS, AHP, PHP, MySQL